Onomasiologiskhed og leksikografi - Farø, Ken (LexicoNordica, 2011)
What is onomasiologicalness? How does it interact with (other) lexicographical concepts? Is it a relevant lexicographical genre criterion? The newcoined term onomasiologicalness makes it easier to more clearly graduate the traditional binarity of the lexicographical genre distinction between semasiological dictionaries on the one hand and onomasiological dictionaries on the other. In this vein, the onomasiologicalness of a number of quite different dictionary types is looked at.